Advances in biblical Hebrew linguistics: data, methods, and analyses - Moshavi, Adina Mosak; Notarius, Tania (Linguistic Studies in Ancient West Semitic, 2017)
"1. The verbless clause in biblical Hebrew: linguistic approaches / edited by Cynthia L. Miller -- 2. Phonology and morphology of biblical Hebrew: anintroduction / by Joshua Blau -- 3. A manual of Ugaritic / by Pierre Bordreuil and Dennis Pardee -- 4. Word order in the biblical Hebrew finite clause: a syntactic and pragmatic analysis of preposing / by Adina Moshavi -- 5. Oath formulas in biblical Hebrew / by Blane Conklin -- 6. Biblical Hebrew grammar visualized / by Francis I. Andersen and A. Dean Forbes -- 7. Time and the biblical Hebrew verb: the expression of tense, aspect, and modality in biblical Hebrew / by John A. Cook -- 8. Diachrony in biblical Hebrew / edited by Cynthia L. Miller-Naude and Ziony Zevit -- 9. The syntax of volitives in biblical Hebrew and Amarna Canaanite prose / by Helene Dallaire -- 10. The relative clause in biblical Hebrew / by Robert D. Holmstedt --11. Language change in the wake of empire: Syriac in Its Greco-Roman context / by Aaron Michael Butts -- 12. Advances in biblical Hebrew linguistics: data, methods, and analyses / edited by Adina Moshavi and Tania Notarius